EFL Students' Experiences of AI-Assisted Reading in Developing Vocabulary Knowledge: A Qualitative Study - La Ode Rasmin; Hikmawati Hikmawati; Siti Rahmatia Kaif (e-Journal of ELTS (English Language Teaching Society), 2026)
The rise of artificial intelligence (AI) has impacted English language training, particularly in vocabulary development and reading instruction. This study investigates how EFL students utilize AI-assisted reading to improve their vocabulary in a Reading for General Purposes course. Ten pupils were purposefully chosen from a single class using a qualitative descriptive method. Students' experiences using AI to comprehend English reading materials were gathered through written interviews via a Google Form with 8 open-ended questions. Braun and Clarke's framework, comprising data familiarization, coding, and theme generation, was used to analyze the data thematically. Six major themes emerged from the findings: AI as a reading comprehension aid; AI's role in developing contextual vocabulary; useful AI features for reading instruction; modifications to students' reading experiences and learning strategies; difficulties and constraints of AI use; and students' affective reactions and attitudes toward AI integration. Overall, the findings show that students' vocabulary, reading comprehension, and confidence are all enhanced by AI-assisted reading. To avoid over-reliance, the study also emphasizes the value of digital literacy and the lecturer's responsibility in directing AI use. To achieve more critical and effective technology-integrated reading instruction in EFL contexts, these findings offer pedagogical insights.